BUSINESS STRATEGY ANALYSIS AND DESIGN FOR STEM CELL THERAPY VENTURES - Victor Sitepu, Hans (Jurnal Gici Jurnal Keuangan dan Bisnis, 2024)
Rapid technological advances in the utilization of stem cells as an alternative treatment for degenerative diseases have prompted numerous parties to launch new start-up enterprises that provide stem cell therapy services to high-income populations. This report offers the findings from a business analysis of one of Indonesia's newly created stem cell therapy service enterprises. This study aims to provide insights and proposals in the form of viable business strategies for stem cell therapy service providers in Indonesia. This study combined descriptive approaches with a qualitative approach. The study's findings showed that the stem cell therapy company under consideration has promising growth prospects. Researchers presented 28 business ideas based on observations, data collecting, interviews, and an in-depth SWOT analysis of the stem cell therapy business endeavor under consideration. It is envisaged that future study will be able to completely examine and compare all stem cell therapy service businesses in Indonesia, providing a more complete view of their potential and performance